Religious overreach at the Supreme Court - Rutledge, Walter Scott (Algora Publishing, 2018)
The U.S. Supreme Court has ceased to be a strictly legal institution, if it ever was one. That's why we see such impassioned political struggles over any appointment of a new Justice. The contentiousness includes, moreover, the nature of the role which the Justices now claim for themselves, that of an originator of new laws and policies. The question is explored here through a careful selection and reassessment of a dozen very interesting and controversial cases.